ASSESSING THE IMPACT OF THE STORM ON SEDIMENT TRANSPORT IN COASTALZONE OF MEKONG RIVER ESTUARY - Cuong, Le Duc; Tu, Tran Anh (Vietnam Journal of Marine Science and Technology, 2016)
In this study, we applied Delft3D model to simulate the sediment transport features in storm conditions in coastal estuary of Mekong river, by which the detailed processes related to sediment transport, erosion - accretion of shoreline are assessed. This paper is a part of the research results of the international cooperation project of protocol Vietnam - United States: “Interaction between hydrodynamic processes in Bien Dong (East Vietnam Sea) and water in Mekong river” (2013 - 2014). The results show that under influences of hydrodynamic factors and wave conditions in storm, when the wind speed is at the level of 6 - 7, sediment transport process is concentrated from zone of 5 m depth toward the coastline, this area will expand outwards from zone of 5 m depth when the wind speed reaches the level of 8 - 9. In surface layer, the average value of sediment concentration is about 0.03 - 0.04 kg/m3. In bottom layer, the maximum value of sediment concentration is about 0.4 - 0.5 kg/m3 (the wind speed is at the level of 8 - 9), and areas of sediment transport are mainly in zone of 5 m depth toward the shoreline.